Answer:
![f_(B): f_(A) = \sqrt{(2)/(1)}](https://img.qammunity.org/2020/formulas/physics/college/wazzc4006fsvqae6c2x44ydmummx12z4e3.png)
Step-by-step explanation:
For pendulum A: Length = L and gravity = g
The frequency of pendulum A is given by
![f = (1)/(2\pi )\sqrt{(g)/(L)}](https://img.qammunity.org/2020/formulas/physics/college/fosurt7i8k9m4z32ijvjst9m59eatt6r7u.png)
Here, f is the frequency, L be the length
... (1)
For pendulum B: Length = 2L, gravity = g
The frequency of pendulum B is given by
.... (2)
Divide equation (1) by (2)
![f_(B): f_(A) = \sqrt{(2)/(1)}](https://img.qammunity.org/2020/formulas/physics/college/wazzc4006fsvqae6c2x44ydmummx12z4e3.png)